AN ANNULLED AWARD CANNOT BE ENFORCED UNDER THE NEW YORK CONVENTION - Faizal Kurniawan (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Arbitral award is final and binding. A concept of “binding” is fundamental in International arbitral award. Nevertheless, the focus commonly concerns about the annulment and/or deferment of International arbitral award so that it could not be implemented. However, the New York Convention does not govern this issue. In addition, international arbitral awards must meet the following requirements: the award is made in the territory other than conflicting countries, and/ or it is not considered a domestic awards in the State where recognition and enforcement is sought. This is important because the enforcement proceedings between foreign and domestic awards are different. This article elaborates the principles of the recognition and enforcement of a foreign award and the grounds or criteria for refusing to enforce an award are limited to the specific defenses i.e. public policy. The party opposing enforcement bears the burden of proofin the existence of the enumerated defenses.Keywords: binding, annullment, deferment, acknowledgement and enforcement of arbitral award.